Vedolizumab for the Management of Refractory Behçet’s Disease: From a Case Report to New Pieces of Mosaic in a Complex Disease - Arbrile, Marta; Radin, Massimo; Rossi, Daniela; Menegatti, Elisa; Baldovino, Simone; Sciascia, Savino; Roccatello, Dario (Frontiers in Immunology, 2021)
Abstract Objectives When treating Behçet’s disease (BD), the anti-TNFαagents have become a standard when conventional immunosuppressive drugs have failed. However, in case ofanti-TNFαagents’ failure options are limited. Based on previous reports of the efficacy of Vedolizumab in IBD we decided to administer Vedolizumab (VDZ) to treat a patient with intestinal BD. Methods We present the case of a 49-year-old female patient with BD. Her clinical manifestations includederythema nodosum, oro-genital ulcers, positive Pathergy test, positive HLA-B51and biopsy-proven intestinal BD. The patient was unsuccessfully treated with conventional immunosuppressive and several biological drugs. Results Treatment with Vedolizumabwas startedintravenously at a dose of 300 mg at 0, 2nd and 6th week and then every four weeks. After the second dose of VDZ the patient reported a marked improvement of intestinal BD. Further, she also experienced an improvement of her arthralgia, erythema nodosumlesions and aphtosis. Clinical remission was achieved after 6 months from VDZ initiation. Conclusion VDZ might represent a valid option for treatment of patients with BD non responsive to standard treatment or anti-TNF agents, in particular in those cases with intestinal involvement.